Application of English Common Law in Malaysia: with reference to derbyshire county council v times newspapers ltd & ORS - Ali Mohamed, Ashgar Ali (Lexis Nexis, 2017)
It will be seen in this article that the Court of Appeal in Malaysia is divided on the issue whether the Derbyshire principle is applicable in this country and thereby raising the issue on certainty of the common law applicable in Malaysia.